2012
DOI: 10.1111/j.1751-1097.2012.01237.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light‐emitting Diode Radiations on Human Retinal Pigment Epithelial Cells In Vitro

Abstract: Human visual system is exposed to high levels of natural and artificial lights of different spectra and intensities along lifetime. Light-emitting diodes (LEDs) are the basic lighting components in screens of PCs, phones and TV sets; hence it is so important to know the implications of LED radiations on the human visual system. The aim of this study was to investigate the effect of LEDs radiations on human retinal pigment epithelial cells (HRPEpiC). They were exposed to three light-darkness (12 h/12 h) cycles,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 22 publications
3
76
0
Order By: Relevance
“…These results suggest that blue light enhances intracellular ROS production on both B16F1 and B16F10 melanoma cells. Chamorro et al () also reported that blue light increase ROS level on human retinal pigment epithelial cells. Superoxide can trigger the chain of reaction to apoptosis (Jancar et al, ).…”
Section: Resultsmentioning
confidence: 90%
“…These results suggest that blue light enhances intracellular ROS production on both B16F1 and B16F10 melanoma cells. Chamorro et al () also reported that blue light increase ROS level on human retinal pigment epithelial cells. Superoxide can trigger the chain of reaction to apoptosis (Jancar et al, ).…”
Section: Resultsmentioning
confidence: 90%
“…Chamorro et al . analyzed human RPE cells irradiated with monochromatic blue (468 nm), green (525 nm), and red (616 nm) LED light, and multichromatic white LED light (CCT not clarified) (5 mW cm −2 ). Significant DNA damage and apoptosis was present in cells treated with blue and white light.…”
Section: Discussionmentioning
confidence: 99%
“…Chamorro et al . also demonstrated that more DNA damage and apoptosis of retinal pigment epithelial (RPE) cells were caused by blue LED light than green and red.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blue LED illumination, which emits light at the short end of the visual spectrum (440-480 nm), has been demonstrated to be the most effective frequency for melatonin suppression compared with conventional lighting technologies (Falchi et al, 2011;West et al, 2011). Finally, looking directly to the source of LED illumination can severely damage retinal cells (Chamorro et al, 2013).…”
mentioning
confidence: 99%